2016
DOI: 10.1038/srep39663
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-Guided Bioinformatics Model for Identifying Autism Spectrum Disorder Diagnostic MicroRNA Biomarkers

Abstract: Autism spectrum disorder (ASD) is a severe neurodevelopmental disease with a high incidence and effective biomarkers are urgently needed for its diagnosis. A few previous studies have reported the detection of miRNA biomarkers for autism diagnosis, especially those based on bioinformatics approaches. In this study, we developed a knowledge-guided bioinformatics model for identifying autism miRNA biomarkers. We downloaded gene expression microarray data from the GEO Database and extracted genes with expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 68 publications
(81 reference statements)
0
23
1
Order By: Relevance
“…Since many key biological processes including the development, differentiation, and cell cycles are regulated by microRNAs, the abnormal expression of microRNAs is often associated with the initialization and progression of many diseases [ 6 , 7 ]. Thus miRNAs usually could serve as suitable biomarkers for many diseases, such as neurodevelopmental disorders [ 8 ], cancer, and cardiovascular disease [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since many key biological processes including the development, differentiation, and cell cycles are regulated by microRNAs, the abnormal expression of microRNAs is often associated with the initialization and progression of many diseases [ 6 , 7 ]. Thus miRNAs usually could serve as suitable biomarkers for many diseases, such as neurodevelopmental disorders [ 8 ], cancer, and cardiovascular disease [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional enrichment analysis results show that 439 GO terms and 128 KEGG pathways are significantly associated with the target genes of the hub miRNAs. Moreover, several significantly enriched GO biological processes and KEGG pathways, including Cell cycle arrest (GO: 0007050), Regulation of immune response (GO: 0050776) ( Gupta et al, 2014 ) ( Ander et al, 2015 ), Nervous system development (GO:0007399) ( Hu et al, 2017 ), NF-kappa B signaling pathway (hsa04064) ( Malik et al, 2011 ), Long-term depression (hsa04730) ( Monday et al, 2018 ), Wnt signaling pathway (hsa04310) ( Shen et al, 2016 ), and gastric cancer (hsa05226) ( Wasilewska and Klukowski, 2015 ) are closely associated with the progression and development of ASD ( Figure 4B ). As for the identified hub miRNA sponges, functional enrichment analysis results indicate that they are significantly enriched in SMAD binding (GO: 0046332).…”
Section: Resultsmentioning
confidence: 99%
“…By binding with messenger RNAs (mRNAs) at the post-transcriptional level, miRNAs as tiny non-coding RNA molecules (∼22 nucleotides) can induce repression or translational inhabitation of mRNAs ( Ambros, 2004 ). Previous studies ( Ander et al, 2015 ; Hu et al, 2017 ; Shen et al, 2016 ) have elucidated that miRNAs participate in several biological processes that are closely associated with ASD, including synaptic plasticity and neuronal development ( Hu et al, 2017 ), immune response ( Ander et al, 2015 ), and signaling pathways ( Shen et al, 2016 ). These studies have also indicated that miRNAs and their corresponding targets could help to uncover ASD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Without the knowledge, we cannot build the precision models, and we even cannot identify the risk factors and the pathogens at the systems level. The building of knowledge base for CCA can help us to connect the reported factors and to build the systems biological model for the investigation of heterogeneity of CCA and to identify the key players or the drivers in different steps of the CCA evolution 91 .…”
Section: The Future Perspectives On Precision Medicine Of Cholangiocamentioning
confidence: 99%